ANALISIS SEKTOR UNGGULAN DAN DAYA SAING WILAYAH KOMODITAS DI KABUPATEN OKU TIMUR - Imam Asngari (Department of Development Economics, Universitas Sriwijaya, 2008)
The purpose of this study to identified basic sector and commodity competitive at the Ogan Komering Ulu Timur municipality. The secondary data used from Biro Pusat Statistik (BPS) to the basic sector identification by Location Quotient Index (LQ) in period 2001-2006 and primary data in 2007 to analysis commodity on regions competitive by Competitive Productivity for Labor Index (CLI). Focusing that analysis are basic sector and basic employment to determinant by competitive region. The result of the research sow that founding basic sector in OKU Timur that is agriculture sector, coals and mining and services. Base on commodity and competitive region, Martapura and Belitang district its has hight competitively on indutries commers, hotels and restaurant, and services. The disstric BP Peliung and Madang Suku II has competitive to genteng industries, coals and mining i.e Mineral and Quarrying Type C Production. The paddy field is a basic coomodity in Buay Madang district and competitive at walet, Pedigree Fowl and Domestic Hens, and rice milling unit. The district Belitang II and Belitang III are has highest competitively at food industries, and transportation. Semendawai Suku III, Semendawai Suku Barat, Semendawai Suku Timur, and Cempaka district its has competitive highest at fish production by cultivated, Fresh Water Pond, Paddy Field and open water, palm oil and Rubber of Smallholders Estate. Key Words: Basic sector, basic employment, location quotient, competitive productivity of labor index.